2001
DOI: 10.1248/bpb.24.291
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional Relationship of in Vitro Mast Cell-Nerve Communication Observed by Confocal Laser Scanning Microscopy.

Abstract: During the last decade there has been an exponential increase in data illustrating that the immune and nervous systems are not disparate entities.1,2) The mast cell-nerve relationship has served as a prototypic association and has provided substantial evidence for bi-directional communication between nerves and immune cells.3) Early studies elegantly described the non-random spatial association of mast cells and nerves in a variety of tissues in which actual membranemembrane contacts could be observed. 4,5) To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Using the murine SCG-RBL cell system as a model of neuron-mast cell association, we showed bidirectional communication between the cells by using either specific neuronal [BK or SV (21)] or mast cell [i.e., anti-IgE antibodies (22)] activators as the initiating stimuli. These studies depended largely on Ca 2ϩ imaging as the index of cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Using the murine SCG-RBL cell system as a model of neuron-mast cell association, we showed bidirectional communication between the cells by using either specific neuronal [BK or SV (21)] or mast cell [i.e., anti-IgE antibodies (22)] activators as the initiating stimuli. These studies depended largely on Ca 2ϩ imaging as the index of cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In addition we studied by atomic force microscopy (AFM) the morphological structure of the interaction between neurites and mast cells (RBL) which was involved in the communication.…”
mentioning
confidence: 99%
“…6) Our findings have implications for the neuroimmune signaling cascade that are likely to occur during airways inflammation, intestinal hypersensitivity, and other conditions in which mast cells feature. [6][7][8] In addition we studied by atomic force microscopy (AFM) the morphological structure of the interaction between neurites and mast cells (RBL) which was involved in the communication. 9) AFM images showed that association between the growth cone of neurites and the RBL cell occurred over ca.…”
mentioning
confidence: 99%
“…Our data illustrated that SCG neurites were activated in response to RBL activation after a lag time (Figure 2) (61,73). In coculture dishes, anti-IgE antibody-or antigen-induced RBL activation was invariably followed by SCG neurite activation.…”
Section: Direct Activation Of Neurites By Atp Released From Mast Cellsmentioning
confidence: 73%